MEASURED AND PREDICTED RATES OF SEDIMENT TRANSPORT IN STORM CONDITIONS - Williams J.J.; Rose C.P. (My University, 2001)
Owing to difficulties in obtaining measurements and to the vagaries of the weather at sea, few field data exist pertaining to sediment mobilisation and transport in storm conditions. Consequently, empirical formulae widely used to predict sediment transport in marine environments remain largely untested in extreme conditions. In the present paper, bedload transport rates estimated from measured rates of bedform migration and measured rates of suspended sediment transport have been compared with predictions from various empirical formulae. Rates of bedload transport inferred from measured rates of ripple migration are found to compare favourably with previous observations and with empirical predictions obtained using the Bijker formula. Measured rates of total sediment transport are found to agree well with predictions from the Soulsby formula. Results show that these formulae are able to predict accurately marine sediment transport in combined wave-current conditions during a storm.
Keywords: BEDLOAD TRANSPORT; SUSPENDED LOAD; WAVE-CURRENT INTERACTION; STORM CONDITIONS